2018
DOI: 10.1007/s11914-018-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

PET-MRI for the Study of Metabolic Bone Disease

Abstract: Purpose of review: This review article attempts to summarize the current state and applications of the hybrid imaging modality of PET-MRI to metabolic bone diseases. The advances of PET and MRI are also discussed for metabolic bone diseases as potentially applied via PET-MRI. b) Recent findings: Etiologies and mechanisms of metabolic bone disease can be complex where molecular changes precede structural changes. Although PET-MRI has yet to be applied directly to metabolic bone disease, possible applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…osteoporosis, osteomalacia, Paget's disease, renal osteodystrophy, and parathyroid disorders. Although still evolving, PET/CT/MRI with NaF or FDG holds promise for the study of metabolic bone diseases (41), not only for earlier detection and optimal treatment, but also the application of preventive measures (42). Several studies have demonstrated the value of NaF-PET in the monitoring of therapy response in osteoporosis, specifically in postmenopausal women (43,44), as the most common metabolic bone disorder.…”
Section: Metabolic Bone Diseasementioning
confidence: 99%
“…osteoporosis, osteomalacia, Paget's disease, renal osteodystrophy, and parathyroid disorders. Although still evolving, PET/CT/MRI with NaF or FDG holds promise for the study of metabolic bone diseases (41), not only for earlier detection and optimal treatment, but also the application of preventive measures (42). Several studies have demonstrated the value of NaF-PET in the monitoring of therapy response in osteoporosis, specifically in postmenopausal women (43,44), as the most common metabolic bone disorder.…”
Section: Metabolic Bone Diseasementioning
confidence: 99%